Analysis of the Curriculum of the State Education System 21 (SPN 21) at the Senior High School Level in Brunei Darussalam - Rio Arjaya; Komarudin Sassi (Program Pascasarjana UIN Sumatera Utara, 2024)
The SPN 21 Curriculum (21st Century National Education System) in Brunei Darussalam is an educational reform implemented in 2009. Its aim is to equip students with 21st-century skills, such as critical thinking, creativity, problem-solving, and technological literacy. This research employs a qualitative descriptive analysis approach through literature study to understand the implementation and impact of the SPN 21 curriculum. The focus of the research includes educational objectives, teaching methodologies, and student learning outcomes. Data was collected from policy documents, research reports, and academic articles. The findings indicate that the implementation of SPN 21 in education has goals and philosophies aimed at creating relevant, high-quality, and adaptive education, as well as developing a flexible curriculum that focuses on core competencies and 21st-century skills. The challenges faced include human resource readiness, infrastructure limitations, and the need for support from various stakeholders.